Towards a time and cost effective approach to water quality index class prediction - Ho J.Y.; Afan H.A.; El-Shafie A.H.; Koting S.B.; Mohd N.S.; Jaafar W.Z.B.; Lai Sai H.; Malek M.A.; Ahmed A.N.; Mohtar W.H.M.W.; Elshorbagy A.; El-Shafie A. (Elsevier B.V., 2023)
Ammonia; Biochemical oxygen demand; Cost effectiveness; Data mining; Decision trees; Dissolved oxygen; Forecasting; Learning systems; Quality assurance; Rivers; Water conservation; Water management; Water quality; Biochemical oxygen demands (BOD); Cost-effective approach; Decision tree modeling; Prediction model; River water quality; Water quality indexes; Water quality parameters; Water quality predictions; River pollution; accuracy assessment; cost analysis; decision analysis; experimental study; hydrological modeling; index method; machine learning; numerical model; parameter estimation; prediction; river management; river water; water quality; Klang River; Malaysia; West Malaysia